Peningkatan Kualitas SDM dan Perekonomian Masyarakat Desa Kwala Serapuh Melalui Pendidikan Berbasis Ekonomi Lokal - Eli Delvi Yanti; Maya Macia Sari; Nurianna Sihombing (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Community service is a movement of self-empowerment process in building a society and making that society better, its character, mindset in order to truly create a better and quality society. The existence of education is a hope to produce a great and qualified generation who are able to take advantage of everything with the aim of advancing the quality of the nation and state. In addition, education is important for the progress of a country in various fields as an example of the economic field. Education can contribute to the economic growth of a country because through education, work productivity will increase and economic growth will increase. In other words, if the quality of education improves, income growth in the poor will be faster. Improving the quality of human resources in the field of education is the key to creating a highly competitive society that will provide insight and challenges as well as opportunities as a long-term investment for the progress of a nation. Education and economy in Kwala Sefragile Village, Langkat Regency, North Sumatra Province still do not meet the criteria in achieving good human resources and education and certainly still need support from various parties in improving the quality of Human Resources and education. For this reason, the team of lecturers and students in the management study program of Universitas Pembangunan Panca Budi contribute to improving the quality of education and Human Resources by conducting community service through socialization, teaching within the scope of general knowledge and academic guidance training through teaching activities by the Kwala Sefragile village community. The activity aims to improve the quality of Human Resources and the economy of the community through education in Kwala Sefragile Village, Langkat Regency.